From adaptive licensing to adaptive pathways: Delivering a flexible life‐span approach to bring new drugs to patients. Issue 3 (4th February 2015) - Eichler, H‐G; Baird, LG; Barker, R; Bloechl‐Daum, B; Børlum‐Kristensen, F; Brown, J; Chua, R; Del Signore, S; Dugan, U; Ferguson, J; Garner, S; Goettsch, W; et al.
<x xml:space="preserve">Abstract</x> The concept of adaptive licensing (AL) has met with considerable interest. Yet some remain skeptical about its feasibility. Others argue that the focus and name of AL should be broadened. Against this background of ongoing debate, we examine the environmental changes that will likely make adaptive pathways the preferred approach in the future. The key drivers include: growing patient demand for timely access to promising therapies, emerging science leading to fragmentation of treatment populations, rising payer influence on product accessibility, and pressure on pharma/investors to ensure sustainability of drug development. We also discuss a number of environmental changes that will enable an adaptive paradigm. A life‐span approach to bringing innovation to patients is expected to help address the perceived access vs. evidence trade‐off, help de‐risk drug development, and lead to better outcomes for patients.